Engaging populations underrepresented in research through novel approaches to consent. Issue 1 (7th March 2018) - Kraft, Stephanie A.; Doerr, Megan
Abstract : The lack of diversity of populations included in genomics databases is an important inhibitor of genomic discovery from bench to bedside. One way to increase the diversity of participants is to ensure that informed consent processes are designed for cultural and linguistic concordance for non‐majority populations. This article describes two case studies of genomics research studies that are using novel approaches to informed consent to increase recruitment and retention of participants from traditionally underrepresented populations: The Cancer Health Assessments Reaching Many (CHARM) study, part of the Clinical Sequencing Evidence‐Generating Research (CSER) consortium, and the All of Us Research Program, part of the Precision Medicine Initiative. We conclude by proposing a community of practice among researchers seeking to improve informed consent to increase diversity in genomics research.